PENDAMPINGAN PENGELOLAAN KEUANGAN SANTRI PANTI ASUHAN NURUL ISLAM TLOGOSARI SEMARANG - Setiyono, Taufiq Andre; Vestari, Mekani; Yusuf, Muhammad; Hamdani, Muliawan; Attiq, Khoirul (Perwira Journal of Community Development, 2025)
Financial issues at the orphanage often being obstacles in implementing their activities, both in terms of budgeting, bookkeeping, administrative arrangements, fund allocation and development needs of orphanage, as well as in their daily activities. This community service aims to provide financial management assistance for students of the Nurul Islam Tlogosari Semarang orphanage. This activity includes socialization and discussion activities. This activity is expected to provide benefits in the form of basic understanding to students in managing their personal finances. In addition, it is hoped that this community service can also provide a simple picture in the process of recording the inflow and outflow of pocket money for each student. Thus, students can evaluate themselves to be better in financial management in the future